Association between weight change and risk of metabolic abnormalities in non-overweight/obese and overweight/obese population: A retrospective cohort study among Chinese adults - Dai, Yanyan; Li, Yujuan; Yang, Shu; Xu, Weiwei; Jia, Hong; Yang, Chao (Frontiers in Endocrinology, 2022)
Objectives: To explore the effects of weight change on the risk of metabolic abnormalities in the Chinese population. Methods: A total of 1895 metabolically healthy adults aged 21–78 years completed anthropometric and biological measurements at baseline (2012) and at an eight year follow-up (2020). Based on absolute weight change and relative weight change, the participants were split into five classes. A Cox proportional hazards regression model was used to estimate the relative risk (RR) and 95% confidence intervals (95% CI) for the risk of metabolic abnormalities using stable weight as the reference group. Stratified analysis was used to explore this relationship in participants with different baseline body mass index (BMI) levels. Results: During the follow-up period, 35.41% of the participants retained a stable weight, and 10.71% had metabolic abnormalities. After covariate adjustment, for every kilogram gained over eight years, the risk of developing metabolic abnormalities increased by 22% (RR: 1.094; 95% CI: 1.063–1.127). Compared with stable weight participants , weight gain of 2–4 Kg and weight gain ≥ 4 Kg exhibited significantly higher risks of metabolic abnormalities, with RR of 1.700 (95% CI 1.150–2.513) and 1.981 (95% CI 1.372–2.859), respectively. A weight gain of ≥ 4 Kg had an opposite effect on the overweight/obesity and non-overweight/obesity groups, with an increased risk of metabolic abnormalities only in the non-overweight/obesity group (RR, 2.291; 95% CI, 1.331–3.942). Moreover, weight loss ≥ 4 Kg significantly reduced the risk of metabolic abnormalities only among overweight/obese adults (RR 0.373; 95% CI 0.154–0.906). Similar results were observed in relative body weight change analyses. Conclusions: Long-term excessive body weight gain is positively associated with an increased risk of metabolic abnormalities among adults with non-overweight/obesity, whereas long-term body weight loss is a protective factor for metabolic health among adults with overweight/obesity.